REKONSTRUKSI WAKAF DALAM PERSPEKTIF HUKUM BERBASIS NILAI KEADILAN - kadarismanto . (UNISSULA, 2014)
Waqf management in Indonesia is required commitment of government, scholars and the public. In addition it needs to be redefined on various matters pertaining to Waqf, including waqf property, benefits and management of Waqf endowment professionally. Treasures that will be used as endowments should not be limited to the non-moving objects, but also moving objects such as Waqf cash (money), stocks and others. In addition Endowments must be submitted to a special body has sufficient competence to be able to manage in a professionaland trustworthy. The research method used in this research is the method of sociological juridical means to identify and conceptualize the law as a social institution that is real and reviewing legislation governing endowments. Based on the results of this research is that: 1) In a political perspective the law, endowments in Indonesia is regulated by three legal instruments: the first with the Instrument of Government Regulation No. 28 of 1977, both with istrumen Impres ie Compilation of Islamic Law (CIL) and the latter with Instruments Act Law No. 41 of 2004; 2) Reconstruction of waqf-based equity value in Act No. 41 of 2004 was added to the formulation in Article 22 Endowment for the economic development of the State capital sources, to invest in sectors that benefit; Article 43 Paragraph (3) was added to the formulation of management of waqf objects by nadzir done productively and must make a profit “; Article67 added to the formulation For every person who intentionally abandon Land Endowment, a maximum of 4 years imprisonment and/or compensation of at least Rp.500.000.000,- (five hundred million rupiah).